Vietnamese Government’s Policy Strategies to Address Human Trafficking (2017–2021) - Soegiharto, Ribka Kristanti; Madu, Ludiro (Nation State: Journal of International Studies, 2025)
Vietnam, as one of the countries in the ASEAN region, has various complex factors that encourage the occurrence of human trafficking problems. This study aims to analyze the strategies of the Vietnamese government in overcoming human trafficking in the 2017-2021 period using qualitative methods. It applies the concept of the anti-trafficking strategy approach as outlined by Cornelius Friesendorf, which emphasizes four key approaches in addressing human trafficking. The study result shows the Vietnamese government's strategies in the 2017-2021 period to implement anti-trafficking strategies through policies to prevent and address the root causes, strengthen and enforce the law, protect victims, and establish partnerships. In these strategies, the government also focuses on victim protection by providing rescue, recovery, education, and economic capacity-building services to non-governmental organizations. There has been progress in policy formation and emphasis on the number of victims. On the other hand, there are challenges, such as a lack of coordination between the central and regional governments, limited resources, and inconsistent law enforcement officials, which serve as obstacles to effectively addressing human trafficking.